Aid budget cuts have dire consequences for malnutrition among the world’s most vulnerable children - Standing Together for Nutrition; Osendarp, Saskia; Bhutta, Zulfiqar; Ahmed, Tahmeed; Brown, Molly; Bryan, Elizabeth; Campbell, Bruce M.; Dinku, Tufa; Ekesa, B.; Fanzo, Jess; Haddad, Lawrence; Ho, Melissa; et al. (Micronutrient Forum, 2025)
Recent aid budgets announced by governments in the US and Europe could cut 2.3 million children off from lifesaving severe acute malnutrition treatment, resulting in 369,000 additional child deaths annually. The US government cuts alone will cause an estimated additional 163,500 annual child deaths that could have been prevented with funding for adequate treatment.